Identification of client iron–sulfur proteins of the chloroplastic NFU2 transfer protein in Arabidopsis thaliana. (2nd April 2020) - Berger, Nathalie; Vignols, Florence; Przybyla-Toscano, Jonathan; Roland, Mélanie; Rofidal, Valérie; Touraine, Brigitte; Zienkiewicz, Krzysztof; Couturier, Jérémy; Feussner, Ivo; Santoni, Véronique; Rouhier, Nicolas; Gaymard, Frédéric; et al.
Abstract : The interaction network of NFU2, a factor required for the maturation of several chloroplastic Fe-S proteins, is delineated, extending its previous assigned function in photosystem I assembly. Abstract: Iron–sulfur (Fe-S) proteins have critical functions in plastids, notably participating in photosynthetic electron transfer, sulfur and nitrogen assimilation, chlorophyll metabolism, and vitamin or amino acid biosynthesis. Their maturation relies on the so-called SUF (sulfur mobilization) assembly machinery. Fe-S clusters are synthesized de novo on a scaffold protein complex and then delivered to client proteins via several transfer proteins. However, the maturation pathways of most client proteins and their specificities for transfer proteins are mostly unknown. In order to decipher the proteins interacting with the Fe-S cluster transfer protein NFU2, one of the three plastidial representatives found in Arabidopsis thaliana, we performed a quantitative proteomic analysis of shoots, roots, and seedlings of nfu2 plants, combined with NFU2 co-immunoprecipitation and binary yeast two-hybrid experiments. We identified 14 new targets, among which nine were validated in planta using a binary bimolecular fluorescence complementation assay. These analyses also revealed a possible role for NFU2 in the plant response to desiccation. Altogether, this study better delineates the maturation pathways of many chloroplast Fe-S proteins, considerably extending the number of NFU2 clients. It also helps to clarify the respective roles of the three NFU paralogs NFU1, NFU2, and NFU3.